β-correction Spectrophotometric Investigation of Copper Chelate Solution with Acid Chrome Blue K Determination of Trace Copper - Gao, Hong-Wen; Chen, Yun-Sheng; Zhang, Peng-Fei (Asian Journal of Chemistry, 2010)
The present work reports uses the updated principle named β-correction theory to analyse spectrophotometrically copper chelate solution with acid chrome blue K (ACBK). The complexation ratio and real molar absorptivity (εr) of chelate formed and effective percentage of ligand ACBK have been worked out easily and acceptably. Using this reaction trace amount of copper has also been determined accurately by β-correction spectrophotometry. The results show that the chelate formed is expressed by Cu(ACBK) at pH 12. Its εr = 1.52 X 10–1 L mol–1 cm–1 at 580 nm. Beer's law is obeyed over the concentration range 0–2.00 mg/L Cu. The relative standard deviations are less than 3.7% and the recovery of copper between 94–108%.